The war on terror and the laws of war : a military perspective - Corn, Geoffrey S. (New York : Oxford University Press, 2014)
Thirteen years after the United States initiated a military response to the terrorist attacks of September 11, 2001, the nation continues to prosecute what it considers an armed conflict against transnational terrorist groups. How the core purpose of the law of armed conflict has influenced operational decisions related to all aspects of the military response to al-Qaeda and associated forces is the focus of this book.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 4, 2014).
Keywords: War on Terrorism, 2001-2009.; Terrorism -- Prevention -- Law and legislation; War (International law); Law; International law